Self-Consciousness of Appearance in Chinese Patients With Cleft Lip: Validation of the Chinese Derriford Appearance Scale 59 (DAS 59) Instrument - Sakran, Karim A.; Song, Sixing; Li, Huo; Pan, Peiyue; Chen, Nan; Zeng, Ni; Chi, Ting; Shi, Bing; Huang, Hanyao; Wang, Yan; Gong, Caixia (Frontiers in Pediatrics, 2022)
Objective To develop a reliable and valid Chinese version of the Derriford Appearance Scale 59 (DAS 59) instrument for assessing the self-consciousness of appearance in Chinese patients with cleft lip. Methods The original DAS 59 instrument was translated into Mandarin, back-translated, and culturally adapted among the Chinese population, following the protocol of the original DAS 59. The validation of the Chinese DAS 59 instrument was estimated on 443 adult participants including 213 subjects with a history of cleft lip with/without palate (CL/P, study group) and 230 normal subjects without facial appearance concern (control group). The reliability was estimated by Cronbach's α coefficient and Guttman's split-half coefficient. Content validity was tested using the Spearman correlation coefficient, while discriminant validity was tested by the Mann–Whitney U test. Results The overall internal consistency of Chinese DAS 59 was excellent; Cronbach's α was 0.951 (α = 0.965 and 0.959 in the study and control groups, respectively). Further, Guttman's split-half coefficient was excellent in the study group (0.935) and control group (0.901). The validity of content was good with an acceptable correlation between all the items and domains. The construct validity through the discrimination was good with a statistically significant difference in most domains between the two groups. Patients with CL/P had more concern about the general self-consciousness and social self-consciousness of appearance. They also showed a good self-concept score. Conclusion The Chinese version of DAS 59 demonstrated acceptable reliability and good construct and discriminant validity. It can be used for the research and assessment of the psychological state and quality of life for Chinese patients with cleft lip as well as other appearance problems and concerns.